The effects of drying temperature on total phenolic content (TPC) and antioxidant activities of Misai Kucing (Orthosiphon stamineus Benth) plants - Siti Noor Yusof (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
The modified spectrophotometric method makes use of the 2,2- diphenyl-1-picrylhydrazyl (DPPH) radical and its specific absorbance properties. The absorbance decreases when the radical is reduced by antioxidants. In contrast to other investigations, the absorbance was measured at a wavelength of 517 nm which disappears upon reduction by an antiradical compound. In addition, a synthetic antioxidant slowly reacts with DPPH reaching a steady state. The use of methanol as extract ant restricts the cellular compounds responsible for scavenging the DPPH radical. Phenolic compounds are known as oxidizing agent that contributes in the reduction process. On the other hand, it accepts an electron during the reaction. However, it is different with the free radical which is involved in the oxidation process. Hence, it is important to act as a reducing agent that donates an electron. The concentration of gallic acid equivalent is the main parameter in order to determine the total phenolic compounds in the sample extracts. From the data, the amount of phenolics can be estimated due to the antioxidants activities. Design of Experiment (DOE) is used to analyze the result. Overall, drying temperature had no significant effect on the TPC content (mg/L gallic acid equivalent) in the plant parts in terms of the free radical scavenging activity.